Effect of calcination temperature on the Cu–ZrO2 interfacial structure and its catalytic behavior in the hydrogenation of dimethyl oxalate. Issue 22 (12th October 2022) - Xu, Yuxi; Huang, Huijiang; Kong, Lingxin; Ma, Xinbin
Abstract : The 5 wt% Cu/ZrO2 catalysts showed satisfying performance in DMO hydrogenation to EG via simply tuning the calcination temperature. The synergistic effect of the Cu 0 –Cu + –ZrO2 interface in activating H2 molecules and carbonyl bonds was elucidated. Abstract : Copper–zirconium catalysts have been extensively applied in the hydrogenation of carbon–oxygen bonds such as in CO2 and esters. However, high-performance Cu/ZrO2 catalysts with low copper loading for dimethyl oxalate (DMO) hydrogenation to ethylene glycol (EG) are seldom reported. Herein, we fabricated 5 wt% Cu/ZrO2 catalysts by a co-precipitation method and investigated the effect of calcination temperature on the catalyst structure and the corresponding catalytic performance. The crystallization and migration of zirconium and copper species are not simultaneous when increasing the calcination temperature, so the elemental composition of Cu and Zr species is different on the surface and in the bulk CuZrO2 solid solution. The crystalline morphology of ZrO2 is transformed from a-ZrO2 to t-ZrO2 and m-ZrO2 and copper dispersion is also changed. The CZ-600 catalyst has the largest copper dispersion, surface area of Cu 0 and Cu + and strongest H2 adsorption ability, which endow this catalyst with the best catalytic performance. However, TOF values are the largest for the CZ-550 catalyst with a larger ratio of Cu +, oxygen vacancies and Zr 3+, which suggests the interfacial synergy between Cu and ZrO2 in DMO hydrogenation. And further increasing the calcination temperature to above 700 °C will cause the aggregation and sintering of copper nanoparticles and deteriorate the hydrogenation reactivity.